Oil Issues of the Smallest Arabic Member of the OPEC - Khartukov, Eugene M. (Newinera Publisher, 2024)
The past, current status and future of the oil sector of the UAE are considered and analyzed. The author uses methods of comparative and systematic analyses, which are implemented for assessing the emirates’ oil in the context of the world, the Middle East, and the Persian Gulf area. The article mainly concludes that the Covid-19 pandemia has seriously hit the UAE oil market (harder than the other sectors of the national economy), however, the pandemia has made inland oil demand (and petroleum imports) of the emirates lower but the domestic crude oil production will unlikely increase in the foreseeable future above 200 kb/d. Still, the federation fares quite well as the OPEC pledged crude oil production cuts are concerned.